2021
DOI: 10.23917/pharmacon.v18i01.12318
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antihiperurisemia Ekstrak Etanol Daun Afrika (Vernonia amygdalina Delile.) pada Mencit Putih Galur Swiss Webster yang Diinduksi Melinjo dan Hati Ayam

Abstract: Hyperuricemic is a condition in which uric acid level in blood exceeds its normal level. Empirically, African leaves (Vernonia amygdalina Delile.) were used to treat diabetic, hypercholesterolemic, fever, hypertension and hyperuricemic by drinking boiled water of African leaves. This in vivo study was performed to determine antihyperuricemic activity of ethanolic extract of African leaves on male mice using the POCT (Point of Care Testing) method. Suspension combination of melinjo and chicken liver juice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Pada penelitian ini, penurunan kadar asam urat yang lebih baik terjadi ketika menggunakan dosis ekstrak yang lebih tinggi, yaitu 400 mg per berat badan. Dosis yang lebih tinggi menyebabkan adanya lebih banyak senyawa aktif atau metabolit sekunder dalam ekstrak, sehingga dapat menurunkan kadar asam urat dengan lebih baik dan dalam waktu yang lebih cepat (Nuari, Renggana, Yuniar, Novitasari, & Lulu, 2021).…”
Section: Journal Of Pharmaceutical Andunclassified
“…Pada penelitian ini, penurunan kadar asam urat yang lebih baik terjadi ketika menggunakan dosis ekstrak yang lebih tinggi, yaitu 400 mg per berat badan. Dosis yang lebih tinggi menyebabkan adanya lebih banyak senyawa aktif atau metabolit sekunder dalam ekstrak, sehingga dapat menurunkan kadar asam urat dengan lebih baik dan dalam waktu yang lebih cepat (Nuari, Renggana, Yuniar, Novitasari, & Lulu, 2021).…”
Section: Journal Of Pharmaceutical Andunclassified
“…Previous studies reported that Vernonia amygdalina has several secondary metabolites, which include alkaloids, phenols, anthraquinones, cardiac glycosides, tannins, terpenoids, saponins, and terpenoids [3]- [5]. Previous studies have also reported that Vernonia amygdalina has several biological activities such as antihyperuricemia [6], antibacterial and antimicrobial [4], antioxidant [7], and inhibition of α-glucosidase enzyme [8].…”
Section: Introductionmentioning
confidence: 99%
“…African leaf ethanol extract contains flavonoids, saponins, and tannins [11] and can be used for antihypertensives the leaves are highly IOP Publishing doi:10.1088/1755-1315/1107/1/012069 2 nutritious and have antioxidants [12]. People use it as a medicine for diabetes, hypercholesterolemia, fever, hypertension, and gout [13].…”
Section: Introductionmentioning
confidence: 99%